Penerapan Storytelling sebagai Kreativitas Berbicara Siswa SMP - Yunidar, Yunidar; Tahir, Muh; Alit Suputra, Gusti Ketut; Efendi, Efendi; Halifah, Nur (SAWERIGADING, 2025)
This study aims to determine the effectiveness of implementing the storytelling method as a means of developing creativity in the speaking skills of eighth-grade students at SMP Negeri 12 Sigi. The study used a quantitative descriptive approach, with data collection techniques including tests (pre-test and post-test), observation, and documentation. The tests were used to measure improvements in students' speaking skills in the aspects of title and content, expression, pronunciation, gesture, creativity, and interaction. Data analysis was conducted by comparing the pre-test and post-test results using a numerical scoring speaking skills assessment rubric. The results showed that the storytelling method significantly improved students' speaking skills and creativity. Before the implementation, most students were in the Poor category, especially in expression and intonation. After the implementation, 50% of students were in the Good category and 40% in the Very Good category, with the most significant improvements in expression, gesture, and interaction. Thus, storytelling has proven effective as an innovative Indonesian language learning method that can increase students' activeness, creativity, and self-confidence. AbstrakPenelitian ini bertujuan untuk mengetahui efektivitas penerapan metode storytelling sebagai sarana pengembangan kreativitas dalam keterampilan berbicara siswa kelas VIII SMP Negeri 12 Sigi. Penelitian menggunakan pendekatan deskriptif kuantitatif dengan teknik pengumpulan data melalui tes (pre-test dan post-test), observasi, dan dokumentasi. Tes digunakan untuk mengukur peningkatan keterampilan berbicara siswa pada aspek judul dan isi, ekspresi, pelafalan, gestur, kreativitas, dan interaksi. Analisis data dilakukan dengan membandingkan hasil pre-test dan post-test menggunakan rubrik penilaian keterampilan berbicara berbasis skor numerik. Hasil penelitian menunjukkan bahwa penerapan storytelling secara signifikan meningkatkan keterampilan berbicara dan kreativitas siswa. Sebelum penerapan, sebagian besar siswa berada pada kategori Kurang, terutama dalam aspek ekspresi dan intonasi. Setelah penerapan, 50% siswa berada pada kategori Baik dan 40% pada kategori Sangat Baik, dengan peningkatan paling menonjol pada aspek ekspresi, gestur, dan interaksi. Dengan demikian, storytelling terbukti efektif sebagai metode pembelajaran inovatif Bahasa Indonesia yang mampu meningkatkan keaktifan, kreativitas, serta rasa percaya diri siswa.